Contextual fear conditioning in virtual reality is affected by 5HTTLPR and NPSR1 polymorphisms: effects on fear-potentiated startle - Glotzbach-Schoon, Evelyn; Andreatta, Marta; Reif, Andreas; Ewald, Heike; Tröger, Christian; Baumann, Christian; Deckert, Jürgen; Mühlberger, Andreas; Pauli, Paul (Frontiers in Behavioral Neuroscience, 2013)
The serotonin (5-HT) and neuropeptide S (NPS) systems are discussed as important genetic modulators of fear and sustained anxiety contributing to the etiology of anxiety disorders. Sustained anxiety is a crucial characteristic of most anxiety disorders which likely develops through contextual fear conditioning. This study investigated if and how genetic alterations of the 5-HT and the NPS systems as well as their interaction modulate contextual fear conditioning; specifically, function polymorphic variants in the genes coding for the 5-HT transporter (5HTT) and the NPS receptor (NPSR1) were studied. A large group of healthy volunteers was therefore stratified for 5HTTLPR (S+ vs. LL carriers) and NPSR1 rs324981 (T+ vs. AA carriers) polymorphisms resulting in four genotype groups (S+/T+, S+/AA, LL/T+, LL/AA) of 20 participants each. All participants underwent contextual fear conditioning and extinction using a virtual reality (VR) paradigm. During acquisition, one virtual office room (anxiety context, CXT+) was paired with an unpredictable electric stimulus (unconditioned stimulus, US), whereas another virtual office room was not paired with any US (safety context, CXT−). During extinction no US was administered. Anxiety responses were quantified by fear-potentiated startle and ratings. Most importantly, we found a gene × gene interaction on fear-potentiated startle. Only carriers of both risk alleles (S+/T+) exhibited higher startle responses in CXT+ compared to CXT−. In contrast, anxiety ratings were only influenced by the NPSR1 polymorphism with AA carriers showing higher anxiety ratings in CXT+ as compared to CXT−. Our results speak in favor of a two level account of fear conditioning with diverging effects on implicit vs. explicit fear responses. Enhanced contextual fear conditioning as reflected in potentiated startle responses may be an endophenotype for anxiety disorders.